Analyzing the Factors Influencing the Implementation of Talent Management at BKPP of Semarang City - Febrian Madina Yustisia; Sri Hartati (Institut Pemerintahan Dalam Negeri, 2025)
This study examines the implementation of talent management at the Semarang City Personnel Education and Training Agency (BKPP), focusing on the gap between the talent pool and the placement of civil servants (ASN). Using a descriptive qualitative approach, data were collected through observations, interviews, and documentation and analyzed through data reduction, presentation, and conclusion drawing. The findings show that talent management has not been fully optimized due to implementation delays, limited supporting infrastructure, and insufficient leadership commitment. Nevertheless, BKPP has undertaken efforts such as improving assessment systems and increasing communication and outreach to organizational leaders. Overall, the implementation of talent management has the potential to enhance ASN professionalism and promote a transparent merit system, but requires strengthened infrastructure, improved human resource capacity, and sustained commitment from all stakeholders.